On comics and legal aesthetics multimodality and the haunted mask of knowing - Giddens, Thomas (Discourses of law, 2019)
"What are the implications of comics for law? Tackling this question, [this book] explores the epistemological dimensions of comics and the way this once-maligned medium can help think about - and reshape - the form of law. Traversing comics, critical, and cultural legal studies, it seeks to enrich the theorisation of comics with a critical aesthetics that expands its value and significance for law, as well as knowledge more generally. It argues that comics' multimodality - its hybrid structure, which represents a meeting point of text, image, reason, and aesthetics - opens understanding of the limits of law's rational texts by shifting between multiple frames and modes of presentation. Comics thereby exposes the way all forms of knowledge are shaped out of an unstructured universe, becoming a mask over this chaotic 'beyond'. This mask of knowing remains haunted - by that which it can never fully capture or represent. Comics thus models knowledge as an infinity of nested frames haunted by the chaos without structure. In such a model, the multiple aspects of law become one region of a vast and bottomless cascade of perspectives - an infinite multiframe that extends far beyond the traditional confines of the comics page, rendering law boundless"--Back cover